Environmental Law: Then and Now - A. Dan. Tarlock (Washington University Journal of Law & Policy, 2010)
Environmental law is both a mature and constantly evolving field of law. While global climate change now dominates environmental discourse,1 the core regulatory regimes that were enacted between 1969 and 1980 (the environmental decade) remain important because their original objectives have been only partially realized. This Introduction places the articles in the historical context of modern environmentalism and environmental law by situating the foundation of environmental law in both the rational and radical 1960s. To better understand the evolution of the law and the challenges we face in adapting environmental law in light of what have we have learned since the late 1960s and early 1970s, we must first examine the era in which the environment statutes were drafted. This Introduction briefly articulates the basic assumptions of this era, including the inherent tensions between rational and radical environmentalism, illustrates how these tensions influenced the first generation of environment law, and, as the articles indicate, continue to influence the debates about reforms.
Keywords: Global warming; Environmentalism; Ecosystem management; Environmental protection